Retrospective Review of Current Nasojejunal Tube Insertion Practice. (19th January 2015) - Sheikh, Natasha; Falkiner, Michelle; Greer, Mary-Louise
Repeated fluoroscopically guided nasojejunal tube (NJT) insertions, particularly in children, can pose health risks through increased radiation exposure. We analyzed frequency of NJT reinsertions and associated radiation exposure through retrospective evaluation of children <18 years at our institution who underwent fluoroscopically guided NJT insertions from 2007 to 2012. Age and weight, reinsertion frequency per patient, radiation dose (dose actual percentage [DAP]), time interval between, and indication for reinsertion were recorded. A total of 252 children (3 days to17 years, 11 months) had 449 NJT insertions. Reinsertions occurred in 105 (41.7%) patients with 14 (5.6%) having ≥5 reinsertions, and 67.6% of reinsertions occurring in patients <1 year. Mean DAP increased with frequency of reinsertion, along with age and weight. Most common indication for reinsertion was a pulled NJT (34.0%). Fluoroscopic NJT reinsertion was most frequent in younger, smaller patients. Self-guided, bedside NJT insertion, and/or earlier instigation of definitive nutritional therapy delivery should be considered.